2018
DOI: 10.3389/fnmol.2018.00188
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation Regulates the Trafficking and Surface Mobility of GluN3A-Containing NMDA Receptors

Abstract: N-methyl-D-aspartate receptors (NMDARs) play critical roles in both excitatory neurotransmission and synaptic plasticity. NMDARs containing the nonconventional GluN3A subunit have different functional properties compared to receptors comprised of GluN1/GluN2 subunits. Previous studies showed that GluN1/GluN2 receptors are regulated by N-glycosylation; however, limited information is available regarding the role of N-glycosylation in GluN3A-containing NMDARs. Using a combination of microscopy, biochemistry, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 61 publications
(85 reference statements)
1
29
0
Order By: Relevance
“…Importantly, our results obtained with hippocampal neurons ‒ which express endogenous GluN2 and GluN3 subunits ‒ support our findings in HEK293 cells; interestingly, however, we found that the change in glycine affinity induced by the S688Y mutation was less profound in neurons compared to HEK293 cells. This discrepancy have several possible explanations, including: (i) the presence of other NMDAR subtypes in hippocampal neurons compared to the subtypes we expressed in HEK293 cells, including triheteromeric 9 , 62 and/or GluN3A-containing NMDARs 10 , 63 ; (ii) possible differences in posttranslational modifications such as glycosylation 64 ; (iii) possible differences in other proteins that interact with NMDARs 65 , and (iv ) the use of different concentrations of glutamate (HEK293 cells) and NMDA (hippocampal neurons).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Importantly, our results obtained with hippocampal neurons ‒ which express endogenous GluN2 and GluN3 subunits ‒ support our findings in HEK293 cells; interestingly, however, we found that the change in glycine affinity induced by the S688Y mutation was less profound in neurons compared to HEK293 cells. This discrepancy have several possible explanations, including: (i) the presence of other NMDAR subtypes in hippocampal neurons compared to the subtypes we expressed in HEK293 cells, including triheteromeric 9 , 62 and/or GluN3A-containing NMDARs 10 , 63 ; (ii) possible differences in posttranslational modifications such as glycosylation 64 ; (iii) possible differences in other proteins that interact with NMDARs 65 , and (iv ) the use of different concentrations of glutamate (HEK293 cells) and NMDA (hippocampal neurons).…”
Section: Discussionmentioning
confidence: 85%
“…Human embryonic kidney 293 (HEK293) cells were maintained in Opti-MEM I media containing 5% (v/v) foetal bovine serum (FBS; Thermo Fisher Scientific). The cells were transfected using Lipofectamine 2000 (Thermo Fisher Scientific) as described previously 64 . After transfection, the HEK293 cells used for electrophysiology were dissociated with trypsin; the cells used for microscopy and biochemistry were cultured without the trypsinisation step in culture media containing 1% FBS, 20 mM MgCl 2 , 1 mM D,L-2-amino-5-phosphonopentanoic acid, and 3 mM kynurenic acid (to prevent cell death caused by excessive activation of NMDARs).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore examined whether the N-terminal and/or C-terminal regions of GluN3A subunits regulate the surface expression of NMDARs by expressing wild-type and mutant GluN1 and GluN3A subunits in COS-7 cells (a cell line derived from African green monkey kidney fibroblast; acronym “COS” is derived from the cells being C V-1 (simian) in O rigin, and carrying the S V40 genetic material) and Human Embryonic Kidney 293 (HEK293) cells (which do not express endogenous GluN subunits), and in cultured hippocampal neurones. Our group 51 and others 52,53 previously reported that GluN1-4a/GluN3A receptors produce larger glycine-induced currents compared to GluN1-1a/GluN3A receptors; therefore, we used the GluN1-4a subunit in our experiments with COS-7 and HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…N-linked glycosylation plays a critical role in protein trafficking and secretion. [32][33][34] From our results, we speculated that loss of aromatic moiety at residue 49 of OPG may directly interfere with N-linked glycosylation, resulting in slow and steady protein trafficking, and extracellular secretion. Indeed, inhibition on N-linked glycosylation by tunicamycin treatment decreased extracellular secretion of OPG in a concentration-dependent manner ( Figure 4E and Figure S4A), where a transient blockade of glycosylation yielded a smeared gel migration pattern of multiple protein bands, observed in mutant OPG (OPG Y49R and OPG Y49A ) ( Figures 2C and 4C).…”
Section: A1crd2 Of Opg Delays Extracellular Transport By Affecting N-mentioning
confidence: 82%